2007
DOI: 10.1540/jsmr.43.55
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed gene networks in cultured smooth muscle cells from normal and neuropathic bladder

Abstract: Neuropathic bladder dysfunction results from abnormal development of the spine, spinal cord injuries, or diseases such as diabetics. Patients with neuropathic bladders often require surgical intervention such as bladder reconstruction to improve incontinence and prevent renal damage. Tissue engineering with ex-vivo cultured bladder cells has been suggested as one means for improving bladder function. However, we previously demonstrated that cultured bladder smooth muscle cells (SMCs) derived from neuropathic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…11 Although previous research showed that integrin subunits in BSMCs were up-regulated in response to over stretch injury, 12 to our knowledge it remained unknown which integrin subunit changes under physiological stretch. Data from the current study clearly reveal that the expression of integrin a4 and integrin av was largely increased but integrin subunits a1, a3, a4, av, b1 and b3 were not affected under physiological stretch.…”
Section: Discussionmentioning
confidence: 93%
“…11 Although previous research showed that integrin subunits in BSMCs were up-regulated in response to over stretch injury, 12 to our knowledge it remained unknown which integrin subunit changes under physiological stretch. Data from the current study clearly reveal that the expression of integrin a4 and integrin av was largely increased but integrin subunits a1, a3, a4, av, b1 and b3 were not affected under physiological stretch.…”
Section: Discussionmentioning
confidence: 93%
“…A restriction to date has been a reliable source of healthy SMCs, as biopsies normally lead to low cell harvest that needs to be expanded at length before therapeutic use [10]. In addition, previous research has shown that SMCs that are obtained from diseased tissue can differ phenotypically and functionally from normal healthy SMCs, which consequently restricts their use [52,53]. The findings of Rodriguez et al (2006) [10], Jack et al (2009) [42], Kima et al (2008) [45] and Yang et al (2008) [46] describe a source of cells to use for SMC applications, as the results show that ADSCs have the potential to differentiate into functional SMCs and consequently may prove a useful source of autologous cells for reconstruction of diseased human organs and tissues containing smooth muscle.…”
Section: Resultsmentioning
confidence: 99%
“…However, several issues currently limit their applicability. Beside their restricted proliferation ability and the loss of contractile phenotype during in vitro culture and expansion [56], there are many obstacles associated with utilizing patients' own SMCs, such as sample size limitation and pathological changes [18,57]. Thus, to overcome these constraints, adult [58], embryonic (ESCs) [59] and induced pluripotent stem cells (iPSCs) [60] have been considered potential candidates for detrusor muscle bioengineering.…”
Section: Detrusor Musclementioning
confidence: 99%
“…However, the use of primary cells is often limited by their short life span, and they cannot be isolated from diseased tissue, for example urothelial progenitors from bladder cancer patients or smooth muscle cells (SMCs) from neuropathic bladders [17,18]. Based on their ability for multilineage differentiation, plasticity, migration and self-renewal, stem cells are being considered suitable candidates to further improve tissue regeneration and to facilitate faster incorporation of transplanted bioscaffolds into the native tissue without the primary cell drawbacks [19,20].…”
Section: Introductionmentioning
confidence: 99%